Performance Evaluation to Provide StaaS to IoT Devices in Fog Computing Environment - Machado, José dos Santos; Silva, Danilo Souza; Fontes, Raphael Silva; Menezes, Adauto Cavalcante; Moreno, Edward David; Ribeiro, Admilson de Ribamar Lima (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2018: Anais do XIX Simpósio em Sistemas Computacionais de Alto Desempenho, 2018)
This work presents the concept of Fog Computing, its theoretical contextualization, the related works, and performsthe analysis of a Fog Computing to provide StaaS (Storage as a Service) on IoT devices using embedded systems platforms,in addition for comparing its results with those obtained by a high-performance server. In this article, we use OwnCloud andBenchmark SmashBox (for data transfer analysis). The results showed that the implementation of this service in embeddedsystems devices can be a good alternative to reduce one of these problems, in this case, the storage of data, which currentlyreaches IoT devices.